2006
DOI: 10.1002/hyp.6281
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Connectivity of Runoff Model (CRUM) to investigate the influence of storm characteristics on runoff generation and connectivity in semi‐arid areas

Abstract: Abstract:Much attention has been given to the surface controls on the generation and transmission of runoff in semi-arid areas. However, the surface controls form only one part of the system; hence, it is important to consider the effect that the characteristics of the storm event have on the generation of runoff and the transmission of flow across the slope. The impact of storm characteristics has been investigated using the Connectivity of Runoff Model (CRUM). This is a distributed, dynamic hydrology model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 28 publications
3
81
1
1
Order By: Relevance
“…Handbook (FEH, 1999), to semi-distributed continuous simulation models, like CLASSIC (Climate and Land Use Scenario simulation in catchments) (Crooks and Davies, 2001) and ARNO (Todini, 1996), to physically-based distributed models, like CRUM3 (Reaney et al, 2007) and SHE (Abbott, 1986a;1986b;Bathurst, 1986). These model classifications were outlined in Chapter 2, and this section explains how these specific models have been applied to flood risk modelling.…”
Section: Application Of Hydrological Models To Investigate Land Managmentioning
confidence: 99%
See 1 more Smart Citation
“…Handbook (FEH, 1999), to semi-distributed continuous simulation models, like CLASSIC (Climate and Land Use Scenario simulation in catchments) (Crooks and Davies, 2001) and ARNO (Todini, 1996), to physically-based distributed models, like CRUM3 (Reaney et al, 2007) and SHE (Abbott, 1986a;1986b;Bathurst, 1986). These model classifications were outlined in Chapter 2, and this section explains how these specific models have been applied to flood risk modelling.…”
Section: Application Of Hydrological Models To Investigate Land Managmentioning
confidence: 99%
“…This adaptive timestep maintains model stability in more computationally intensive parts of the simulation. CRUM-3 has been used in several catchments for both academic (Reaney et al, 2007;Reaney, 2008;Lane et al, 2009) and commercial (Conlan et al, 2005) purposes.…”
Section: Crum-3 (Connectivity Of Runoff Model)mentioning
confidence: 99%
“…It implies that even suffering the similar rainfall, the observed discharges may not be identical, but must be much similar in modeling. Reaney et al (2007) concluded that storms with similar amounts of total rainfall but with varying rainfall allocation can generate very different discharge patterns, depending on the storm characteristics. Pebesma et al (2007) applied QPBRRM, a quasi-physically based rainfall-runoff model, on R-5 catchment with 72 storm events and concluded that by considering event variables (e.g.…”
Section: Validation and Inter-comparison Among Eventsmentioning
confidence: 99%
“…Foremost are the models SCS (Michaud and Sorooshian, 1994;Symeonakis and Drake, 2004), VIC (Abdulla and Lettenmaier, 1997;Stephen et al, 2010), KINEROS (Michaud and Sorooshian, 1994;Hernandez et al, 2000;Al-Qurashi et al, 2008), TOPMODEL (Candela et al, 2005), MIKE SHE (McMichael et al, 2006), CRUM (Reaney et al, 2007), HBV (Masih et al, 2010;Jia and Sun, 2012), IHACRES (Jakeman et al, 1990;Jakeman and Hornberger, 1993;Evans and Jakeman, 1998;Dye and Croke, 2003;Croke et al, 2006;McIntyre and Al-Qurashi, 2009), HEC-HMS (Halwatura and Najim, 2013), and SWAT (Hernandez et al, 2000;Yu et al, 2011;Perrin et al, 2012). Some of these, however, share certain problems that reduce their effectiveness in semiarid regions.…”
Section: Introductionmentioning
confidence: 99%